Transient tachypnoea of the newborn (TTN) requiring mechanical ventilation - case report & review of literature - Iqbal, ASM; Begum, LN (Pulse, 2010)
Transient tachypnea of the newborn (TTN) is usually a benign and self-limited disease of the newborns and the prognosis is generally excellent. It is believed to be resulting from incomplete resorption of fluid from the lungs of the newborn. Infants present with respiratory distress, requiring oxygen supplement for 2-3 days. However some infants with severe symptoms and hypoxaemia may need prolonged oxygen supplement and sometimes mechanical ventilation. Here we present a borderline preterm baby with TTN, who required mechanical ventilation. DOI: 10.3329/pulse.v3i1.6549 Pulse Vol.3(1) July 2009 p23-24